Digital learning in Malaysian schools - Mohd Salim, Mohd Nur Fitri; Mohamad Yusuf, Asmahanim; Halim, Nurul Syafawani; Mohd Salim, Mohamad Safwat Ashahri (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The incorporation of online learning technologies into Malaysian schools, accelerated by the COVID-19 pandemic, represents a significant shift in teaching and learning methods. The widespread availability of modern digital tools has expanded the scope of learning beyond the traditional classroom. Students can now participate more actively through various interactive tools and platforms. Traditional and mobile applications, including DELIMa, Quizizz, Google Classroom, and many others, are used more frequently as part of the curriculum and offer personalised self-paced learning, which transitions away from content delivery (Mustapha et al., 2024). Teachers have adopted the role of guides and facilitators, and students can engage with the content through quizzes, videos, and group projects, which enable them to learn critical skills needed in the 21st century (Wan Mustapha, 2019).